Relationship Between Nutritional Status and Physical Fitness of Players At SSB Kancil Mas Karawang Aged 17 Years - Gunawan, Reki; Gemael, Qorry Armen; Aulia, Dany; Wijaya, Habibi Hadi; Setiawan, Arief (UNIVERSITAS NEGERI MAKASSAR, 2024)
The purpose of this study was to test whether there was a relationship between nutritional status and physical fitness levels of SSB Kancil Mas Karawang. This type of research is a correlation study. This study was conducted in February 2024 at the Kancil Mas Karawang Football School. The population in this study were all SSB Kancil Mas Karawang U-16 soccer players totaling 15 people. The sampling technique used a purposive sampling technique. The test instruments used were 1) measuring nutritional status to determine the player's body mass index and 2) measuring the Indonesian physical fitness test (TKJI) to determine the player's physical fitness. The data analysis technique in this study used simple correlation analysis or product moment. Based on the results of this study, there is a significant relationship between nutritional status and physical fitness among SSB Kancil Mas Karawang soccer players, with the results of a strong relationship.